A Conserved Core of Programmed Cell Death Indicator Genes Discriminates Developmentally and Environmentally Induced Programmed Cell Death in Plants. Issue 4 (5th October 2015) - Olvera-Carrillo, Yadira; Van Bel, Michiel; Van Hautegem, Tom; Fendrych, Matyá¡; Huysmans, Marlies; Simaskova, Maria; van Durme, Matthias; Buscaill, Pierre; Rivas, Susana; S. Coll, Nuria; Coppens, Frederik; Maere, Steven; et al.
Abstract : Programmed cell death occurring as an integral part of plant development is characterized by the transcriptional activation of a distinct core of conserved cell death-associated genes. Abstract: A plethora of diverse programmed cell death (PCD ) processes has been described in living organisms. In animals and plants, different forms of PCD play crucial roles in development, immunity, and responses to the environment. While the molecular control of some animal PCD forms such as apoptosis is known in great detail, we still know comparatively little about the regulation of the diverse types of plant PCD . In part, this deficiency in molecular understanding is caused by the lack of reliable reporters to detect PCD processes. Here, we addressed this issue by using a combination of bioinformatics approaches to identify commonly regulated genes during diverse plant PCD processes in Arabidopsis ( Arabidopsis thaliana ). Our results indicate that the transcriptional signatures of developmentally controlled cell death are largely distinct from the ones associated with environmentally induced cell death. Moreover, different cases of developmental PCD share a set of cell death-associated genes. Most of these genes are evolutionary conserved within the green plant lineage, arguing for an evolutionary conserved core machinery of developmental PCD . Based on this information, we established an array of specific promoter-reporter lines for developmental PCD in Arabidopsis. These PCD indicators represent a powerful resource that can be used in addition to established morphological and biochemical methods to detect and analyze PCD processes in vivo and in planta.